2014
DOI: 10.1007/s10875-014-0116-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Mutation in MAGT1 and Progressive Multifocal Leucoencephalopathy in a 58-Year-Old Man with XMEN Disease

Abstract: XMEN disease (X-linked immunodeficiency with Magnesium defect, Epstein-Barr virus infection and Neoplasia) is a novel primary immune deficiency caused by mutations in MAGT1 and characterised by chronic infection with Epstein-Barr virus (EBV), EBV-driven lymphoma, CD4 T-cell lymphopenia, and dysgammaglobulinemia [1]. Functional studies have demonstrated roles for magnesium as a second messenger in T-cell receptor signalling [1], and for NKG2D expression and consequently NK- and CD8 T-cell cytotoxicity [2]. 7 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…Meanwhile, the patient is on oral magnesium supplementation treatment. Corroborating findings in 9 previously described patients with MAGT1 mutations (Table 2) [2][3][4], immunological analyses of our patient revealed selective CD4 lymphopenia, resulting in a CD4:CD8 T cell ratio of b 1 in the patient, as well as low numbers of granulocytes (Table 1). Normal neutrophil and CD4 T lymphocyte numbers were observed in the patients' two healthy siblings (data not shown).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Meanwhile, the patient is on oral magnesium supplementation treatment. Corroborating findings in 9 previously described patients with MAGT1 mutations (Table 2) [2][3][4], immunological analyses of our patient revealed selective CD4 lymphopenia, resulting in a CD4:CD8 T cell ratio of b 1 in the patient, as well as low numbers of granulocytes (Table 1). Normal neutrophil and CD4 T lymphocyte numbers were observed in the patients' two healthy siblings (data not shown).…”
supporting
confidence: 87%
“…In 2011, Li et al [1] reported a novel primary immunodeficiency associated with loss-of-function mutations in MAGT1, encoding the Mg 2+ -channel MAGT1, and accordingly termed X-linked immunodeficiency with magnesium defect, EBV infection and neoplasia (XMEN syndrome). Lenardo and colleagues demonstrated that MAGT1-deficiency abrogates an Mg 2+ flux required for T cell signaling and activation [1][2][3]. Here, we describe an adolescent with a novel hemizygous mutation in exon 4 of MAGT1 (c.555dup) who presented with severe autoimmune disorders and Hodgkin lymphoma mimicking autoimmune lymphoproliferative syndrome (ALPS).…”
mentioning
confidence: 95%
“…Fortunately, there has recently been an attempt to standardize the HRCT findings in CVID‐ILD . Only sporadic CVID patients with lung samples were included here (abnormal T cells excludes a diagnosis of CVID in our cohort), as most children with antibody failure in our cohort have been found recently to have a CID on next‐generation sequencing studies .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 10 reported patients to date [62–64] all are male and the frequency of female carriers has yet to be determined [42,61]. XMEN patients have normal growth and development indicating that the previous hypothesis that mutations in MagT1 are one cause of X-linked intellectual disability [57] was premature [65].…”
Section: Protein Hypoglycosylation Causes a Family Of Human Diseasesmentioning
confidence: 99%